Saikosaponin-d Attenuates Irinotecan-Induced Intestinal Toxicity via TAK1/NF-κB Pathway and Enhances Antitumor Efficacy - Zheng P; Ma R; Liu X; Song L; Ma B; Zou G (Journal of Inflammation Research)
Peng Zheng,1,2,* Rui Ma,1,3,* Xiaoya Liu,2 Luda Song,3 Bing Ma,1,* Guijun Zou1,* 1Department of General Surgery, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China; 2Department of General Surgery, The Sixth Medical Center of Chinese PLA General Hospital, Beijing, 100048, People’s Republic of China; 3Medical School of Chinese PLA, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bing Ma, Department of General Surgery, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China, Email mabingcaowei1983@sina.com Guijun Zou, Department of General Surgery, The First Medical Center of Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China, Email zougj301@163.comPurpose: Saikosaponin-d (SSD), a bioactive triterpenoid saponin derived from Bupleurum species (a traditional Chinese medicine), is recognized for its gastrointestinal protective properties. This study investigates the therapeutic potential and mechanisms of SSD against irinotecan (IRI)-induced intestinal mucositis.Methods: Using a CT26 colorectal cancer Syngeneic mouse model (BALB/c mice), we evaluated the synergistic antitumor efficacy of SSD combined with IRI. Concurrently, the protective effects of SSD against IRI-induced intestinal toxicity were assessed in vivo (BALB/c mice) and in vitro (lipopolysaccharide (LPS)-stimulated Caco-2 cells). In vivo evaluations included monitoring body weight changes, diarrhea severity, colon length, and histopathological alterations. Mechanistic insights into the anti-inflammatory and antioxidant effects were elucidated through RT-qPCR, Western blotting, immunohistochemistry, and oxidative stress marker analysis.Results: SSD significantly mitigated IRI-induced intestinal injury, as demonstrated by attenuated body weight loss, improved diarrhea scores, and preserved colon length. Histopathological examination revealed that SSD protected intestinal epithelial integrity and enhanced barrier function. Mechanistically, SSD reduced oxidative stress by modulating antioxidant enzyme activities (SOD, GSH-Px) and suppressing lipid peroxidation (MDA levels). Furthermore, SSD inhibited proinflammatory cytokine production (IL-6, TNF-α, IL-1β) via downregulation of the TAK1/NF-κB pathway in both IRI-treated mice and LPS-challenged Caco-2 cells.Conclusion: Our findings demonstrate that SSD alleviates IRI-induced intestinal mucositis through suppression of the TAK1/NF-κB signaling cascade, highlighting its potential as an adjuvant therapy to enhance the safety profile of IRI-based chemotherapy.Keywords: intestinal mucositis, oxidative stress modulation, gastrointestinal protection, cytokine reduction, TAK1/NF-κB pathway